Between Positivism and Substantive Justice: Predictors of Pancasila Value Actualization Among State-Judiciary Actors - Indrayani; Henry Halim; Imran; Imeldalius (Arkus, 2025)
The Indonesian Constitution anchors adjudication in Pancasila, mandating a balance between legal certainty, utility, and social justice, yet how state-judiciary actors actualize these ideological values in practice remains empirically underexplored, particularly in resource-rich regions beset by agrarian and socio-economic conflict. This study analyzed the predictors and contextual variation of Pancasila value actualization among judicial actors in a resource-rich province in Sumatra, Indonesia. A convergent parallel mixed-methods design combined a structured survey of 215 legal apparatus across three anonymized court jurisdictions (urban, coastal, agrarian) with interviews of 15 judges and 9 prosecutors and 45 purposively selected verdicts (2021-2025). Validated multi-item scales measured actualization, substantive justice orientation, legal positivism orientation, restorative justice practice, and institutional constraint; reliability was good to excellent (Cronbach's α 0.861-0.911). Overall actualization was constrained (mean 2.05 of 5). Multiple regression explained 53.0% of the variance (F(7,207) = 33.39, p < 0.001); substantive justice orientation was the strongest positive predictor (β = 0.467, 95% CI 0.356 to 0.577), followed by restorative justice practice (β = 0.240), whereas legal positivism (β = -0.205) and institutional constraint (β = -0.133) were negative. Actualization differed by court typology (F(2,212) = 12.91, p < 0.001, η² = 0.109), being highest in the agrarian court (Cohen's d = 0.75 versus urban). Institutional constraint partially mediated the justice-orientation pathway (Sobel z = 2.31, p = 0.021). Actualization is therefore a contextual, modellable negotiation rather than uniform application; embedding Pancasila-based progressive interpretation in judicial training and protecting judges from annulment-driven anxiety could strengthen substantive justice.